The fungal RABOME: RAB GTPases acting in the endocytic and exocytic pathways of Aspergillus nidulans (with excursions to other filamentous fungi). Issue 1 (3rd April 2021) - Pinar, Mario; Peñalva, Miguel A.
Abstract: RAB GTPases are major determinants of membrane identity that have been exploited as highly specific reporters to study intracellular traffic in vivo. A score of fungal papers have considered individual RABs, but systematic, integrated studies on the localization and physiological role of these regulators and their effectors have been performed only with Aspergillus nidulans. These studies have influenced the intracellular trafficking field beyond fungal specialists, leading to findings such as the maturation of trans‐Golgi (TGN) cisternae into post‐Golgi RAB11 secretory vesicles, the concept that these RAB11 secretory carriers are loaded with three molecular nanomotors, the understanding of the role of endocytic recycling mediated by RAB6 and RAB11 in determining the hyphal mode of life, the discovery that early endosome maturation and the ESCRT pathway are essential, the identification of specific adaptors of dynein‐dynactin to RAB5 endosomes, the exquisite dependence that autophagy displays on RAB1 activity, the role of TRAPPII as a GEF for RAB11, or the conclusion that the RAB1‐to‐RAB11 transition is not mediated by TRAPP maturation. A remarkable finding was that the A. nidulans Spitzenkörper contains four RABs: RAB11, Sec4, RAB6, and RAB1. How these RABs cooperate during exocytosis represents an as yet outstanding question. Abstract : This review describes how systematic studies on RAB proteins in Aspergilllus nidulans, complemented with contributions from other model filamentous fungi, have served to delineate the composition and physiological roles of the fungal RABOME